Longitudinal study of humoral immunity against SARS-CoV-2 of health professionals in Brazil: the impact of booster dose and reinfection on antibody dynamics - Franco-Luiz, Ana Paula Moreira; Fernandes, Nubia Monteiro Gonçalves Soares; Silva, Thais Bárbara de Souza; Bernardes, Wilma Patrícia de Oliveira Santos; Westin, Mateus Rodrigues; Santos, Thais Garcia; Fernandes, Gabriel da Rocha; Simões, Taynãna César; Silva, Eduardo Fernandes E.; Gava, Sandra Grossi; Alves, Breno Magalhães; de Carvalho Melo, Mariana; et al. (Frontiers in Immunology, 2023)
The pandemic caused by SARS-CoV-2 has had a major impact on health systems. Vaccines have been shown to be effective in improving the clinical outcome of COVID-19, but they are not able to fully prevent infection and reinfection, especially that caused by new variants. Here, we tracked for 450 days the humoral immune response and reinfection in 52 healthcare workers from Brazil. In-fection and reinfection were confirmed by RT-qPCR, while IgM and IgG antibody levels were monitored by rapid test. Of the 52 participants, 19 (36%) got reinfected during the follow-up period, all presenting mild symptoms. For all participants, IgM levels dropped sharply, with over 47% of them becoming seronegative by the 60th day. For IgG, 90% of the participants became seropositive within the first 30 days of follow-up. IgG antibodies also dropped after this period reaching the lowest level on day 270 (68.5±72.3, p<0.0001). Booster dose and reinfection increased the levels of both antibodies, with the interaction between them resulting in an increase in IgG levels of 130.3 arbitrary units. Overall, our data indicate that acquired humoral immunity declines over time and suggests that IgM and IgG antibody levels are not associated with the prevention of reinfection.